Oxime ether lipids containing hydroxylated head groups are more superior siRNA delivery agents than their nonhydroxylated counterparts. (September 2015) - Gupta, Kshitij; Mattingly, Stephanie J; Knipp, Ralph J; Afonin, Kirill A; Viard, Mathias; Bergman, Joseph T; Stepler, Marissa; Nantz, Michael H; Puri, Anu; Shapiro, Bruce A
Aim: To evaluate the structure–activity relationship of oxime ether lipids (OELs) containing modifications in the hydrophobic domains (chain length, degree of unsaturation) and hydrophilic head groups (polar domain hydroxyl groups) toward complex formation with siRNA molecules and siRNA delivery efficiency of resulting complexes to a human breast cancer cell line (MDA-MB-231).Materials & methods: Ability of lipoplex formation between oxime ether lipids with nucleic acids were examined using biophysical techniques. The potential of OELs to deliver nucleic acids and silence green fluorescent protein (GFP) gene was analyzed using MDA-MB-231 and MDA-MB-231/GFP cells, respectively.Results & conclusion : Introduction of hydroxyl groups to the polar domain of the OELs and unsaturation into the hydrophobic domain favor higher transfection and gene silencing in a cell culture system.